Improvement of thermocyclic treatment technology to increase wear resistance of gears - D. M. Berdiev; A. A. Yusupov; A. Kh. Abdullaev; G. M. Kamilova (Литьë и металлургия)
The technology of thermocyclic treatment of fine‑module gears has been improved, which makes it possible to increase their wear resistance by 30–40 %. Gears were subjected to preliminary cyclic heating and subsequent impulse hardening. In all cases of hardening, a martensitic structure is formed, which provides high rigidity of the material. The sizes of martensitic plates depend on the heating temperature during quenching. During cyclic heat treatment up to a temperature of 450 °C, the sizes of austenite grains and martensite plates did not depend on temperature.